Production performance and economics of Khaki Campbell ducks in the backyard system of rearing at the NICRA-adopted village in Darrang district of Assam (Indian Journal of Animal Production and Management, 2024)
This research paper evaluates the production  performance and economic viability of Khaki  Campbell ducks in backyard farming systems at  NICRA-adopted flood-prone village in the Darrang  district of Assam. The study investigates key  productivity metrics such as egg production rates,  growth performance, and survival rates, alongside  economic factors including input costs, labor  requirements, and market returns. The integration  of Khaki Campbell ducks, renowned for their high  egg yield and resilience, is explored as a  sustainable agricultural practice that aligns with the  objectives of the National Innovations in Climate  Resilient Agriculture (NICRA) project. Findings  indicate that Khaki Campbell ducks perform well in  backyard systems, with notable egg production and  robust growth. The mean body weight at 30 weeks  was 1.82±8.4 kg, and the average age at first egg  was 163±4.3 days. Throughout the study period,  the mean egg production was 185.5±5.1, and the  mean mortality rate was 12.5%. Economically, the  practice is viable with a B:C ratio of 2.07, showing  favorable returns compared to the investment and  labor involved. The research highlights the potential  for these ducks to enhance household income and  nutritional security, contributing to greater  agricultural resilience against climate variability.  These insights provide valuable guidance for  policymakers and rural development initiatives  aiming to promote sustainable and climate-resilient  agriculture in similar regions.
Keywords: Khaki Campbell ducks; ackyard system; production performance; production; economic viability; Assam